Assessment of Eocene, Paleocene and Cretaceous source rocks in the West Feiran area, offshore Gulf of Suez, Egypt - Abd-Allah, Zakaria M.; Abdullah, Wan Hasiah; Abdel-Fattah, Mohamed I. (Elsevier, 2019)
The study area is located in the West Feiran area, offshore Gulf of Suez, Egypt. This gulf is a well-known petroleum prolific basin that was formed from Late-Oligocene to Early Miocene times. This study focuses on evaluating the source rocks of Eocene (Thebes Formation), Paleocene (Esna Formation) and Cretaceous (Sudr, Brown Ls., Matulla, Wata and Raha formations) of GS 197–2 and WFA-1 wells based on total organic carbon (TOC), Rock-Eval pyrolysis, vitrinite reflectance (VR), and seismic data. In this study, Thebes, Sudr and Brown Ls. are considered to have fair to very good TOC (up to 4.05 wt%) that are characterized by Type II kerogen (mainly oil-prone) and mixed Type II/III kerogen (swamp oil and gas-prone), but haven't reach the peak of hydrocarbon generation at present depth of GS 197–2 well. On the other hand, Esna, Matulla, Wata and Raha formations have relatively lower TOC (only up to 1.15 wt%). For these formations the quality of the organic matter is represented by mixed Type II/III and Type III kerogen (mainly gas-prone), but have reached the maturation and generation stages in both wells with the presence of indigenous hydrocarbons detected. Depth-structure maps of these source rocks based on seismic data interpretation indicate that the mature source rocks located in the NW direction are so much deeper than the others in the study area. Understanding regional variations of Eocene, Paleocene and Cretaceous source-rock maturities which largely depend on burial depth will help to reduce the risk for future exploration drilling within the Gulf of Suez. © 2019 Elsevier B.V.